Changing health workforce attitudes to promote improved physical health in mental health service users: Keeping our Staff in Mind (KoSiM). (28th January 2020) - Rosenbaum, Simon; Ward, Philip B.; Baldeo, Rishi; Fibbins, Hamish; Jarman, Rebecca; Lederman, Oscar; Perram, Amy; Poole, Josephine; Rossimel, Elisa; Smith, Gabriella; Teasdale, Scott; Wade, Tammy; et al.
Abstract: Issue addressed: People living with mental illness die on average 15 years earlier than the general population, primarily due to preventable and premature cardiovascular disease. Lifestyle interventions can be effective in reducing cardiovascular risk, yet mental health services do not routinely provide targeted lifestyle interventions. Exposing mental health staff to lifestyle interventions prior to targeting patients may be critical to changing culture and improving patient outcomes. This study aimed to improve the physical health of mental health staff through a targeted lifestyle intervention. Methods: A pragmatic single‐arm intervention study was conducted in a public mental health service, including inpatient and community settings, in Sydney, Australia. Participants in this study were n = 212 clinical and non‐clinical staff. A five‐session individualised lifestyle intervention (delivered over 5 weeks) incorporating physical activity and nutritional counselling was delivered by multidisciplinary teams. Participants were assessed at baseline, following the intervention, and at follow‐up (mean = 16.7 weeks). The primary outcome was the barriers, attitudes, knowledge and confidence regarding screening, promoting and intervening to improve physical health outcomes of patients (M‐BACK questionnaire). Secondary outcomes included anthropometric measures, cardiorespiratory fitness, sedentary time and nutritional intake. Repeated measures ANCOVAs were performed. Results: A total of 212 staff (79% female) participated in this study. M‐BACK total score significantly increased from baseline to follow‐up ( P < .001). Waist circumference, sedentary time and total energy intake all significantly decreased (all P 's < .001) and cardiorespiratory fitness significantly increased ( P < .001). Conclusion: A brief lifestyle intervention for staff of a public mental health service may increase the capability of the participants to improve their own physical health. So what?: Improving staff health may be an important strategy in improving the uptake and/or the effectiveness of lifestyle interventions targeting mental health service users.